PERANCANGAN ENVIRONMENTAL GRAPHIC DESIGN MUSEUM SEPULUH NOPEMBER SURABAYA SEGABAI PENDUKUNG PROGRAM SURABAYA CITY TOUR - Hidayat, Royyan; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: The goal of the design of Environmental Graphic Design Museum Ten November Surabaya is as a supporting program of Surabaya City Tour tour. The study was conducted using qualitative research methods is to conduct in-depth understanding of the objects that can be done by observation, interviews, documentation and literature to obtain the data used to support the design of Environmental Graphic Design. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. From the data analysis found some keywords that refer to design communication strategies that will be used to reach the intended target audience. After analyzing the data, found a design concept or keyword of "Flashback" which has the meaning of a flashback. Description of the concept is intended that the visitors were able to identify an iconic design for a museum Ten November Surabaya in various media which include Environmental Graphic Design. Results of this scheme is to support the Surabaya City Tour tourist program which is a program owned by the tourist city of Surabaya as the town hero.Keywords: History, Heroic, Flashback